2019
DOI: 10.1002/cbic.201900490
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling Two Consecutive Hydroxylations: Mechanisms of Aromatic Hydroxylations Catalyzed by Flavin‐Dependent Monooxygenases for the Biosynthesis of Actinorhodin and Related Antibiotics

Abstract: Flavin‐dependent monooxygenases are ubiquitous in living systems and are classified into single‐ or two‐component systems. Actinorhodin, produced by Streptomyces coelicolor, is a representative polycyclic polyketide that is hydroxylated through the action of the two‐component ActVA‐5/ActVB hydroxylase system. These homologous systems are widely distributed in bacteria, but their reaction mechanisms remain unclear. This in vitro investigation has provided chemical proof of two consecutive hydroxylations via hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 24 publications
0
11
0
2
Order By: Relevance
“…This system has recently been demonstrated in vitro to catalyze an additional C-8 oxygenation (Figure ). This study also showed that Med-7 (a C-6 FMO) solely affords a trihydroxynaphthalene intermediate leading to DHK 6 (Figure ). An S. coelicolor engineered strain in which the C-6 oxygenase genes were replaced with med -7 led to produce 7 and 8 , together with KAL 4 .…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…This system has recently been demonstrated in vitro to catalyze an additional C-8 oxygenation (Figure ). This study also showed that Med-7 (a C-6 FMO) solely affords a trihydroxynaphthalene intermediate leading to DHK 6 (Figure ). An S. coelicolor engineered strain in which the C-6 oxygenase genes were replaced with med -7 led to produce 7 and 8 , together with KAL 4 .…”
Section: Resultsmentioning
confidence: 89%
“…24 This observation is reasonably explained by the monofunctionality at the C-6 oxygenation of Med-7 (Figure 1) to accumulate DHK 6, which is converted to its AcCys adducts as unwanted metabolites in the ACT pathway. A lactonizing conversion of DHK 6 to KAL 4 was demonstrated, 40,41 indicating its mechanism is most likely via a hydroquinone formation (Figure S5).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…[63] Within the biosynthesis of the polyaromatic pyranonaphthoquinone antibiotic actinorhodin (23), two consecutive hydroxylations take place at the C6 and C8 positions via atwo-component FMO (Figure 8). [64] Sequential dihydroxylation within the natural product pathway of saxitoxin has recently been shown to be catalysed by two Rieske oxygenases.Each enzyme was responsible for aregioand stereoselective hydroxylation from b-saxitoxinol to yield 11-b-hydroxysaxitoxin (24). [65] Furthermore in the biosyntheses of platensimycin (25)a nd platencin (26), an on-haem diiron monooxygenase hydroxylates at the C5 b-position facilitating facile diversification of these natural products.…”
Section: Hydroxylationmentioning
confidence: 99%
“…[83] Enzymvarianten wurden kürzlich für die stereoselektive Lacton-Carben-Insertion entwickelt (Schema 10). Durch die Einführung dieser funktionellen Gruppe waren zahlreiche Derivate des Sequiterpenlactonamins (61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74) in hohen Enantio-und Diastereoselektivitäten zugänglich. [82] Kürzlich wurde über die Konstruktion von P411-Enzymen für die C(sp 3 )-H-Aminierung berichtet.…”
Section: Nicht-natürliche Oxyfunktionalisierungenunclassified